A ritualização das passagens da vida : desafios para a prática litúrgica da Igreja - Mansk, Erli (2009)
The ritualizing of life passages from the perspective of the liturgical practices of the Church is the subject of this dissertation. Rites of passage are present in every culture. They mark identical transitions in human life and help people and groups to go through important changes in the bio-psycho-social cycle and to cope with the tensions caused by the passages. The rites of passage work as a seam between the different phases of life. What are the relevant passages in today s life and how the churches deal or could deal with them are leading questions in the investigation of the subject. Having as principal reference the theorist Arnold van Gennep, the first chapter investigates the anthropological fundaments of the rites of passage. This author studies in exhaustion the rituals that come with life passages as pregnancy and birth giving, birth and childhood, initiation or entrance in adult life, marriage and death, and defines an universal principle that helps to understand the individual and collective passages. This chapter also inquires about traditional rituals of passage still present in modern society and reflects about the changes in the modern and post-modern society and the consequences of those changes to the rituals of passage. The second chapter studies the passages and the ritualizing of life passages in our days. The method of qualitative social research was used for this study, applying an individual interview to ten people chosen by the researcher. The results of this research accentuate the human need for ritualizing life passages. At the end of the second chapter are presented the challenges that the ritualizing of life passages brings to Christian liturgy today. The third chapter studies the ritualizing of passages in the Church. In the first section the subject is examined from the current liturgical practice of the rituals of passage, having as reference the example of the Evangelical Church of the Lutheran Confession in Brazil (IECLB). In the second section, the theme is investigated from the liturgical practices selected from the origins of the Christian Church and the ritual practices that surrounded them. In this chapter s conclusion are collected consequences for the ritualizing of life passages in the current liturgical practice. Having as a starting point the methods of liturgical inculturation developed by liturgist Anscar Chupungco, the fourth chapter proposes a method for the ritualizing of life passages in the Church in modern times and applies this method to some chosen passages. It is a method that can be used to any passage, in any circumstance. The ritualizing of life passages brings many challenges to the Church in modern times. There are many life passages today that need rituals. By ritualizing life passages, the Church responds to a fundamental human need: it meets the most urgent needs in life and answers disquieting human questions.